Experimental Study on Demineralization of Coal with Pseudomonas Mendocina Strain B6–1 Bacteria to Obtain Clean Fuel. Issue 5 (October 2014) - Singh, Asha Lata; Singh, Prakash K.; Kumar, Aniruddha; Yadav, Akhilesh; Singh, Mahendra P.
We present the results of the investigations carried out on the demineralization of coal of the Rajmahal Gondwana basin of India using Pseudomonas mendocina strain B6–1. Petrographically these coals are characterized by high concentration of inertinite macerals with subordinate amount of vitrinite and liptinite macerals. The mineral matter content occurs in high concentration which gives a high ash yield. This coal contains relatively high content of major, minor and trace elements when compared with the Clarke values in coal. After the bacterial treatment a considerable reduction in the elemental content of oxygen, hydrogen and sulphur was seen. Reduction in the ash content (>5%) was achieved and variable degrees of removal of the various major, minor and trace element concentration was also noticed. Nearly 59% removal of Mn, 53% of Na, 13% of Fe was achieved among the major/minor elements while nearly 54% of As, 41% of Cd, 39% of Cu, 34% of Ni, 32% of Zn, 13% of Cr, 43% of Co and 66% of Pb could be removed. Arsenic, Fe and Ca have a strong positive correlation with the ash removal percentage indicating that the samples having increased concentration of these elements are prone to demineralization with Pseudomonas mendocina strain B6–1. Whereas the elements like Ni, Zn, Cr and Cu maintain a strong negative correlation with the ash removal percentage indicating that their enrichment could have hampered the process of demineralization.